Biological pretreatment of oil palm empty fruit bunch by a local isolate of Schizophyllum commune ENN1 for production of fermentable sugars - Arbaain, Enis Natasha Noor (2018)
Oil palm industry in Malaysia plays a major role in national socio-economic development. In line with the expansion of the industry, oil palm biomass is generated abundantly from the plantations and mills. Oil palm empty fruit bunch (OPEFB) is the most abundant lignocellulosic biomass generated from palm oil mill, composed of 25-44% cellulose, 25-28% hemicellulose and 19- 27% lignin. The cellulose and hemicellulose components can be converted into fermentable sugars after being pretreated by either physical, chemical, physicochemical, biological or combination of these pretreatment methods. Currently, physicochemical pretreatment is the most common pretreatment method used to pretreat and convert OPEFB into fermentable sugars. However, this type of pretreatment utilised chemicals that lead to environmental issues and high operational cost. Therefore, biological pretreatment by fungi has been considered as an alternative to pretreat OPEFB as it is environmental friendly and requires low cost for the process. The first objective in this study was to evaluate the feasibility of Schizophyllum commune ENN1 in removing lignin of OPEFB through biological pretreatment. The second objective is to investigate the significant parameters affecting the biological pretreatment of OPEFB by S. commune ENN1 for fermentable sugars production through one-factor-at-a-time (OFAT) method.